ANALISIS KESULITAN MEMBACA PERMULAAN PADA TEMA 7 SUBTEMA 1 SISWA KELAS 1 SDN BULAKAMBA 02 - R, Ainun; Mudzanatun, Mudzanatun; Wardana, M. Yusuf (Tunjuk Ajar : Jurnal Penelitian Ilmu Pendidikan, 2022)
The reading ability of school students at elementary school level currently has a low tendency. Therefore, the focus of this research is to analyse first grade students’ reading difficulties. The goal to be achieved in this study is to analyze the difficulty of beginning reading of first grade students of SD Negeri Bulakamba 02. This research method uses qualitative research methods. The subjects of this study were the principal and first grade teachers and students at SD Negeri Bulakamba 02. The data collection techniques were obtained from observations, interviews, and tests. The results of the analysis and discussion of the data obtained that the implementation of offline learning and the initial reading test carried out can determine the analysis of the difficulty of reading beginning in grade 1 SD Negeri Bulakamba 02. This is evidenced by the achievement of learning effectiveness, namely 1) Initial reading test 2) lesson plan and syllabus successfully implemented in teaching and learning activities 3) methods, models and approaches that are successfully applied in learning activities. Based on the results of this study, the suggestion that can be conveyed is that students who are not fluent in reading should always get used to reading and special attention from parents and teachers, so that first grade students of SD Negeri Bulakamba 02 are able to read fluently and not spell.